The materialization, in Brazilian educational law, of the duty to educate for citizenship in the scope of university education: An overview of cross-cutting themes - Wanderlei Rodrigues , Horácio; André Birnfeld, Carlos (Revista Pedagogía Universitaria y Didáctica del Derecho, 2023)
This article is the result of an exploratory, documentary research on the following problem: how does university education, by its rules, materialize the constitutional duty, referred to in article 205, to prepare for being a citizen? Its main objective, therefore, is to demonstrate how Brazilian law materializes the obligation of education for citizenship in the context of university education. Therefore, with an overview of education for citizenship at the beginning of Brazilian citizenship, which culminates with education for Brazilian citizenship, the best strategy to materialize the themes of education for citizenship in Brazil, the best strategy to materialize the themes of education for Brazilian citizenship Based on various norms, born within or outside the educational law. From this perspective, it brings each of these themes, allowing the analysis at the end of a panoramic view on the material perspective, in the constitutional scope of Brazilian university education, of the duty to prepare for being a citizen.